A review on recent development and application of radiation curing - Sheel Wali A.; Kumar S.; Khan D. (My University, 2025)
Compared to traditional coating processes, radiation curing is different. It takes only a few seconds to get a dry, fully cured film because of the nearly rapid cure and lack of solvents. Two technologies namely Electron Beam (EB) and Ultraviolet (UV) are used in radiation curing. Compared to EB curing, UV curing is a widely accepted technology at present. In the last two decades, UV radiation curing emerges as a well-accepted technology. The main application areas of this technology include industries related to manufacturing, architecture, coating, and electronics. Factors responsible for the popularity of this technique include rapid curing, a high rate of productivity, and low cost. EB curing being costly therefore UV technology is preferred for industrial production. Another reason for the acceptance of this technique is its versatile nature which allows UV coating to be applied on a variety of substrates like plastic, silica, metal, wood, and many more. The present review aims at advancement in the area of radiation curing technology. The study begins with an overview of radiation curing technology development, followed by the mechanism involved in curing. For a better understanding of the process, types of radiation curing methods are also explained. Moreover, the paper provides a detailed advancement in the radiation coating area. Further, emphasize is also made on the leftover thrust area to be explored for increasing the potential of the technology. © 2023 Elsevier Ltd. All rights reserved.